Integrasi Nilai–Nilai Kemanusiaan pada Pembelajaran Matematika dan IPA Sebagai Pendidikan Karakter yang Aktif dan Kreatif - Ni Wayan Putu Suardani (Cetta: Jurnal Ilmu Pendidikan, 2018)
Character formation is one of the national educational goals as set out in article I.UU Sisdiknas year 2003. During this time at the formal level of school tends to character education only transformed through a particular lesson such as religion, Pancasila and character only. Though Character education can be integrated with other subjects such as Mathematics and Science. This literature review aims to describe the integration of character education in Mathematics and Science lessons. This literature review provides a formulation of how character education can be integrated in Mathematics and Science lessons. With the integration of character education to some of these lessons support the achievement of our naisonal education is the development of the potential of learners to have intelligence, personality and noble character.